Personality's Time Perspective as a Resource for Overcoming the Identity Crisis at Different Stages of Life Realization - E.M. Meshcheryakova; A.V. Seryy; M.S. Yanitskiy (Социальная психология и общество)
Objective. Investigating the role of personality's time perspective in overcoming the identity crisis and determining its potential as a resource of personal growth at different stages of life realization. Background. The growth of identity crisis manifestations in modern conditions determines the necessity to search for new directions of psychological work on its prevention and effective resolution. The available theoretical data on the presence of interrelation between temporal and identification characteristics allows to consider the content features of personality's time perspective as a resource for overcoming the identity crisis. Study design. A set of diagnostic techniques aimed at studying the features of a personality's time perspective and the specifics of the manifestations of experiencing identity crises allowed us to collect data on samples formed in accordance with age periods. The primary data were subjected to a comparative analysis of the average values for the studied characteristics and a comparison of the features of the correlation relationships between the indicators of the time perspective and the identity crisis. Later, using the regression analysis of the analysis, the assumption was confirmed about the influence of time perspective indicators on the level of experiencing an identity crisis in the selected age groups. Also, using regression analysis, the hypothesis was tested that the variability of the time perspective in different age groups is conditioned by indicators of stress in crisis areas of life realization. Participants. The study involved 139 people aged 16 to 55 years. The total sample was divided into groups according to age periods: older adolescence (15-17 years, 38 people), adolescence (18-22 years, 47 people), early adulthood (23-29 years, 26 people), maturity/late adulthood (30-55 years, 28 people). All groups were equalized by gender. Measurements. Zimbardo's ZTPI time perspective methodology (modified by A. Syrtsova, E.T. Sokolova, O.V. Mitina); “Crisis Identity Questionnaire” by N.V. Dmitrieva and N.A. Samoilik; questionnaire of crisis events and experiences by V.R. Manukyan; methodology for the study of professional identity and personal identity by L.B. Schneider. The methods of statistical analysis (correlation analysis, Mann-Whitney U Test, Kruskal–Wallis test, regression analysis) were used in the processing of the obtained data. Results. Belief in a just world increases political trust; belief in a dangerous world reduces it. Political trust positively predicts readiness to participate in various forms of normative political activity. The presence of cross-cultural differences in the characteristics of the model between the Russian and Ukrainian samples is established. Conclusions. Content characteristics of the personality's time perspective are an important potential resource for overcoming the identity crisis. It has selective significance at different stages of life realization determining the age-specific features of a possible “therapeutic target” within the framework of psychological influence.